Assessment rubric for research report writing: A tool for supervision - Bukhari, Nurliyana; Jamal, Jamilah; Ismail, Adibah; Shamsuddin, Jauriyah (Universiti Utara Malaysia Press, 2021)
Purpose – Assessment rubric often lacks rigor and is underutilized. This article reports the effectiveness of the use of several assessment rubrics for a research writing course. Specifically, we examined students’ perceived changes and observed changes in their Chapter 1 thesis writing as assessed by supervisors using an existing departmental rubric and a new task-specific rubric.